Study of a Biparametric Family of Iterative Methods - Campos, B; Cordero, Alicia; Magreñán, Á. Alberto; Torregrosa, Juan Ramón; Vindel, P (Abstract and Applied Analysis, 2018)
The dynamics of a biparametric family for solving nonlinear equations is studied on quadratic polynomials. This biparametric family includes the -iterative methods and the well-known Chebyshev-Halley family. We find the analytical expressions for the fixed and critical points by solving 6-degree polynomials. We use the free critical points to get the parameter planes and, by observing them, we specify some values of with clear stable and unstable behaviors.
Keywords: Scopus